Determination of Haptoglobin in relation to metabolic indicators in hormonally synchronized Awassi sheep (Damascus University Journal of agriculture sciences, 2021)
This study was carried out to ascertain the changes of haptoglobin in relation to some blood metabolites during various physiological stages (Pregnancy – Lactation – Weaning). Blood samples were collected by jugular venipuncture from 4 ewes, 2-4 years, selected randomly from 34 hormonally synchronized Awassi ewes under the same nutritional and ecological conditions. Haptoglobin was determined using the ELISA method.  Levels of glucose, total protein, cholestrol and urea were measured using a spectrophotometer.The overall means of Glucose, total Protein, Cholestrol, Urea and Haptoglobin were 53.86 mg/dL – 68.26 g/L – 1.51 mmol/L – 29.68 mg/dL – 153.93 µg/mL, respectively. Haptoglobin exhibited significant differences (p>0.05) during the two weeks of pregnancy as compared to the firt period of pregnancy. The means of Glucose, total Protein, Cholestrol and Urea during pregnancy were non significantly (p>0.05). However, during lactation and weaning the means showed significant differences (p
Keywords: Awassi sheep; Haptoglobin; Blood metabolites